Multilingual Intermediate-Task Training for Cross-Lingual Transfer in Multimodal Models - Assignee Research (Assignee Research, 2026)
This paper studies zero-shot cross-lingual transfer of vision-language models. Specifically, we focus on multilingual text-to-video search and propose a Transformer-based model that learns contextualized multilingual multimodal embeddings. Under a zero-shot setting, we empirically demonstrate that performance degrades significantly when we query the multilingual text-video model with non-English sentences. To address this problem, we introduce a multilingual multimodal pre-training strategy, and
Machine-generated literature synthesis.